Mineralogia de sedimentos ricos em fósforo e cobre - Tonello, Maurício Sonda (2019)
The agriculture sediments usually are enrich in contaminants, and are easily transferred to water bodies. The mineralogical composition of these sediments affect the transport capacity and adsorption/desorption behavior of this contaminants in the environment. In this sense, we will study sediments from different locations (Brazil and USA), with different associated ions (Cu and P), to understand the effect of the mineralogical composition on the sediments behavior in two different environments (stream channel and a lake). The study was divided in two parts: i) field study on copper sediments from a century-old vineyard (southern Brazil), ii) field study on P sediments present in Lake Superior - USA. Vineyard received large amounts of copper, so we estimate a copper rich sediment production. The aim of this study was to evaluate the mineralogical composition of the sediments and to relationship with the copper forms present in the sediment and stream channel water. A rich mineralogical mixture was present at the vineyard and also in the exutory, which was composed of: mica, kaolinite, illite, rutile, hematite, quartz, calcite, magnesite, albite and anortite, and copper minerals. The suspended sediments present in the vineyard area showed high concentrations of total copper (9.16 mg L-1), exchangeable (2.81 mg L-1) and soluble (1.82 mg L-1). However, in the exutory the suspended sediments were rich only in total copper. The second study, presented the P lability of the sediments from Lake Superior. The relationship of P forms with the sediment mineralogy, and the geochemical characterization of these sediments remains poorly understood. The aim of this study is to provide information on the P lability of Lake Superior sediments, and to associate this information with the mineralogical composition and geochemical characterization of these sediments. Samples were collected from the input load (river bed), shoreline erosion, and Lake Bottom. The sediments were composed of minerals of low reactivity and minerals of high reactivity with P, such as oxides and clay minerals. The concentration of total phosphorus in the sediments of the input load, shoreline erosion and Lake Bottom were very high. However, labil phosphorus was less than 10% of the total. More than 80% of the phosphorus was associated with organic matter compounds and carbonate minerals, with low availability to biota. The sediments have a low concentration of bioavailable phosphorus to biota due to the presence of highly reactive minerals with the potential to adsorb P. The results suggest that the sediments act as: i) long-term phosphorus sink (P from Lake Superior), ii) sediments act as a copper stock for the environment, and can become a source of copper for the environment. Both sediment behaviors were strongly influenced by their mineralogical composition, in addition to their geochemical aspects. The mineralogical composition of the sediments rich in P and Cu is a determining factor in the sorption capacity of the ions associated with the sediments, and the information generated by the mineralogical and geochemical analyzes is fundamental in the studies of contaminated sediment behavior